The golden triangle: the internet of things, blockchain, artificial intelligence - U. A. Vishniakou (Системный анализ и прикладная информатика)
The subject of research is the analysis of the integration of the Internet of Things (IOT), blockchain and individual artificial intelligence technologies. The purpose of the article is to show the advantages of sharing the Internet of Things, blockchain, machine learning and neural networks on a number of developed systems. Blockchain is able to provide a structure for transaction processing and coordination of interacting devices in the Internet of Things networks. The problem that prevents the use of artificial intelligence applications and the Internet of Things is vulnerability. Blockchain solves it through three functions: conducting transactions through a reliable payment mechanism without intermediaries; creating indexed records that are protected from changes; distributed storage of information in a public database. Examples of the development of IoT networks for product quality control, monitoring and analysis of audio information, IT diagnostics of patients with neurological diseases, which integrate technologies of IOT, machine learning, neural networks, blockchain, smart contracts.